2006
DOI: 10.1073/pnas.0603806103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aldehyde dehydrogenase and retinoid signaling induces the expansion of human hematopoietic stem cells

Abstract: Aldehyde dehydrogenase (ALDH) is an enzyme that is expressed in the liver and is required for the conversion of retinol (vitamin A) to retinoic acids. ALDH is also highly enriched in hematopoietic stem cells (HSCs) and is considered a selectable marker of human HSCs, although its contribution to stem cell fate remains unknown. In this study, we demonstrate that ALDH is a key regulator of HSC differentiation. Inhibition of ALDH with diethylaminobenzaldehyde (DEAB) delayed the differentiation of human HSCs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
344
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(363 citation statements)
references
References 41 publications
9
344
0
5
Order By: Relevance
“…15, 16). In particular, a functional role of ALDH was recently shown, in which diethylaminobenzaldehyde, a specific inhibitor of ALDH, deregulated human HSC self-renewal by interfering with endogenous retinoic acid biosynthesis (17). These data suggested that ALDH may regulate HSC function and is a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 94%
“…15, 16). In particular, a functional role of ALDH was recently shown, in which diethylaminobenzaldehyde, a specific inhibitor of ALDH, deregulated human HSC self-renewal by interfering with endogenous retinoic acid biosynthesis (17). These data suggested that ALDH may regulate HSC function and is a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3][4][5][6][7][8][9] Recent studies have pointed to high aldehyde dehydrogenase (ALDH) activity as a candidate CIC characteristic. [10][11][12][13][14][15][16][17][18][19][20] ALDH oxidizes retinol to retinoic acid in the early stages of stem cell differentiation. 11 High ALDH activity is detected in both physiological stem cells, such as hematopoietic and neural stem cells, 21,22 and CICs of human multiple myeloma, acute myeloid leukemia, and cancers of the lung and breast, 10,[12][13][14][15][16][17] indicating that ALDH activity may be a common marker for both normal and malignant stem cell populations.…”
mentioning
confidence: 99%
“…However, when the RA pathway is inhibited by a dominant negative RARα mouse HSC repopulation is also supported [174]. Diethylaminobenzaldehyde, an inhibitor of aldehyde dehydrogenase, the enzyme that is responsible for RA synthesis, induced a 3.4-fold of increase of repopulating cord blood HSCs after 7 d of culture, as determined by SCID repopulation assays [175,176]. Together, these results suggest that RA is an important modulator of HSC homeostasis.…”
Section: Retinoic Acid Antagonistmentioning
confidence: 90%